THE EFFICIENCY OF PHYSIOTHERAPY IN THE TREATMENT OF LUMBAR DISCOPATHY IN ELDERLY PATIENTS - Cătălina-Mihaela Dascălu; Marius Neculăeș; Lucaci Paul (Sport şi Societate)
Lumbar pain is one of the most common pathologies encountered among the population. With advancing age, the predisposition to this type of pain increases, which can lead to a decrease in the quality of life.The present study was carried out on a group of 10 patients aged between 70 and 83 years, clinically diagnosed with lumbar discopathy.The recovery program consisted of specific physical therapy exercises associated with massage and medium frequency currents.The obtained results highlight the fact that the pain level decreased significantly following the functional rehabilitation protocol, and the mobility of the lumbar spine improved.The conclusions of the study emphasize the importance of physiotherapy programs in association with massage and medium frequency currents, in terms of improving the symptoms specific to lumbar discopathy in the elderly patient.